FROM CONCEPTION TO TEXT: PARADOXES OF INCOMPLETENESS (“POEM WITHOUT A HERO”, SKETCHES OF A BALLET LIBRETTO AND “PROSE ABOUT A POEM”) (Филологический класс, 2019)
Three unfinished texts by Akhmatova (“Poem without a Hero”, sketches of a ballet libretto for “A Poem without a Hero” and “Prose about a Poem”) became the object of the paper. According to our hypothesis, these works go back to a primary idea, the traces of which are found in their poetic semantics. Hence, the goal of the study is to identify the “residual” traces of this idea in the texts, to trace the dynamics of its implementation and to determine the ways of its implementation in the semantic structure of these works. Being formed at the junction of literary studies and psychology, the goal predetermined the methodology related to the psycholinguistic researches. The methodological base of the article was the idea of N. I. Zhinkin on the “language of inner speech” as a material substrate of primary conception of utterance. The paper shows that the non-verbal sensual components of the “Poems without a Hero” primary conception, associated with visual and auditory onset, were enhanced in texts. The deployment of a polymodal primary conception in different modes into a linear speech product is accompanied by the inevitable loss of meaning. In order to compensate for the loss of meaning when translating an internal image into a verbal plan, Akhmatova uses three strategies: semantic, communicative and intertextual. Semantic strategy includes the nominative aspect, involving the use of images, which, by the degree of saturation with personal meanings, are similar to the inner word, and the plot aspect, which implies the connection of polymodal images with different plot deployment options. Intertextual strategy appears as a means of fixing the original non-verbal meanings. Communicative strategy, connected primarily with the “Poem without a Hero”, causes Akhmatova’s close attention to the reader’s reception, which is caused by the complex polymodal specificity of the Poem’s text in relation to which Akhmatova herself becomes a reader. Thus, the heterogeneity of the original units of the common idea, to which the analyzed works go back, dictates a mixture of genre-generic modes, determines the semantic structure of their images, and determines the fundamental incompleteness of these texts.